Modelling phagosomal lipid networks that regulate actin assembly - Kuehnel, Mark (2015)
Background: When purified phagosomes are incubated in the presence of actin under appropriate conditions, microfilaments start growing from the membrane in a process that is affected by ATP and the lipid composition of the membrane. Isolated phagosomes ar. - DFG [Da 208/7-2, TR34]; BMBF ; Irvington Institute CRI ; FEDER [POCI, PPCDT/BIA- BCM/55327/2004]; Alexander von Humboldt Foundation ; CONICET. - We thank J. Brouwers and B. Helms from Univ. Utrecht, Holland for communicating unpublished data on lipids in LBP phagosomes. This work was generously supported by DFG (Da 208/7-2; TR34), BMBF (Hepatosys, TD and JR; PathogenomikPlus, RS), the Irvington In